2020
DOI: 10.1177/1879366519900996
|View full text |Cite
|
Sign up to set email alerts
|

China’s engagement with Kazakhstan and Russia’s Zugzwang: Why is Nur-Sultan incurring regional power hedging?

Abstract: Grappling with the contemporary topos of a Sino-Russian Entente, Kazakhstan is caught between a delicate long-term peer-competition and potentially a structural rivalry involving the two Eurasian Leviathans, China and Russia. Acknowledging this perspective, Nur-Sultan is inducing hedging dynamics, fishing for a better range of net benefits, while playing a significant fulcrum role central to the regional geopolitical and geo-economic matrix. Although Russia is retaining the prevailing role in the security doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Drawing on neo-Gramscianism and neoliberal institutionalism, the authors suggested a notable shift in regional hegemony, proposing that China, bolstered by the strengthening of the BRI, could emerge as a hegemon shaping the 'forms of state' in Kazakhstan. Ohle, Cook, and Han's (2020) research delved into the complex geopolitical dynamics involving Kazakhstan, Russia, and China, centering on the BRI and the Shanghai Cooperation Organization (SCO). Kazakhstan's nuanced diplomatic approach, aligning with Russia while strategically recognizing China for additional benefits, underscored its diplomatic agility.…”
Section: The Dynamics Of the Belt And Road Initiativementioning
confidence: 99%
“…Drawing on neo-Gramscianism and neoliberal institutionalism, the authors suggested a notable shift in regional hegemony, proposing that China, bolstered by the strengthening of the BRI, could emerge as a hegemon shaping the 'forms of state' in Kazakhstan. Ohle, Cook, and Han's (2020) research delved into the complex geopolitical dynamics involving Kazakhstan, Russia, and China, centering on the BRI and the Shanghai Cooperation Organization (SCO). Kazakhstan's nuanced diplomatic approach, aligning with Russia while strategically recognizing China for additional benefits, underscored its diplomatic agility.…”
Section: The Dynamics Of the Belt And Road Initiativementioning
confidence: 99%
“…Preserving its alignments with Moscow, Kazakhstan considers rapprochement with China as valuable option in the overall framework of its developmental strategy that presupposes keeping and even expanding various forms of bilateral and multilateral cooperation. The hedging strategy has allowed Kazakhstan not to become client state of any of the two hegemons promoting its own political and economic interests, and clearly asserting and protecting its sovereignty (Ohle et al, 2020 Vanderhill et al (2020).…”
Section: Mistrust Hedging and The Cost Of Dominancementioning
confidence: 99%